Sampah Sebagai Energi Terbarukan Berbasis Aplikasi Game Edukasi - Ida Betanursanti; Galih Mahardika Munandar; Alifta Dicasani (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Litter is a very disturbing object in the environment. Public awareness of waste management is still minimal. The government, together with several communities, has tried to utilise it, but waste accumulation remains a significant problem. Entertaining educational efforts are needed to help the public understand proper waste management. In line with the government's programme to promote the use of new and renewable energy, waste can be used as renewable energy, depending on its classification. This research aims to create an entertaining and accessible educational model application in the digital age that utilises waste as renewable energy based on educational games. Tests were carried out using classical statistical tests, including validity tests, reliability tests and Spearman correlation tests. The results obtained from the questionnaires given to the users who completed the trial showed that 4 items were not valid: Q4, Q18, Q29 and Q31. The results of the reliability test showed that out of 28 data tested, the value was very high at 0.946. The correlation test concluded that learnability is correlated with memorability and satisfaction, while satisfaction is correlated with errors